1983
DOI: 10.1007/bf00399894
|View full text |Cite
|
Sign up to set email alerts
|

In vivo induction of neoplastic growth in nude mouse connective tissue adjacent to xenografted human tumors

Abstract: Induction of neoplastic growth of murine stroma cells within the human tumor xenograft was observed after serial passage of CEA and beta 2-microglobulin producing human colonic SLu tumor xenografts in nu/nu BALB/c mice. Mouse tumors within the human tumor xenografts were identified using specific immunohistologic staining techniques for mouse histocompatibility marker or human CEA. These mixed tumors could be distinguished from normal human tumor xenografts by a different relationship between development of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Remarkably, only the murine sarcoma cells were metastatic in mice, indicating the transfer of full neoplastic traits to the benign murine mesenchymal cells. The induction of stromal tumors in host animals after the xenotransplantation of human epithelial cancers was confirmed by other studies, and it was observed that the mechanism, although unclear, resembled a viral-like transfer [167][168][169].…”
Section: The Genometastatic Hypothesissupporting
confidence: 61%
“…Remarkably, only the murine sarcoma cells were metastatic in mice, indicating the transfer of full neoplastic traits to the benign murine mesenchymal cells. The induction of stromal tumors in host animals after the xenotransplantation of human epithelial cancers was confirmed by other studies, and it was observed that the mechanism, although unclear, resembled a viral-like transfer [167][168][169].…”
Section: The Genometastatic Hypothesissupporting
confidence: 61%
“…Each cell type may possess different growth rates and react differently to an administered drug. Further, there are many reliable reports in the literature of human xenografts serially passed in vivo transforming adjacent mouse cells into fibrosarcoma-like malignancies [4-8]. Drugs tested on such samples would generate false and misleading data.…”
Section: Introductionmentioning
confidence: 99%
“…Another line of espousing data is derived from experiments of transplantation of tumor tissues into normal animals [202][203][204]. According to Staab [205] and Goldenberg [206], during 1905-1907 Ehrlich, Apolant, Loeb, Bashford, and a few others had reported in German language that transplantation of mouse mammary carcinoma into other mice could culminate with sarcomatous transformation of the recipient's stromal cells. Actually, in the 1902 Loeb had already noticed that the regrowing tumors in the recipient animals were sarcomas although the original tumors implanted were carcinomas [207], which suggests a possibility that the tumors occurring in the recipient animals may not really be a regrowth of the grafted tumor but may rather be a new tumor derived from a different cell lineage.…”
Section: Dissenting Evidence 2: Altered Extracellular Milieu May Init...mentioning
confidence: 99%
“…Actually, in the 1902 Loeb had already noticed that the regrowing tumors in the recipient animals were sarcomas although the original tumors implanted were carcinomas [207], which suggests a possibility that the tumors occurring in the recipient animals may not really be a regrowth of the grafted tumor but may rather be a new tumor derived from a different cell lineage. Unfortunately, the importance of these earlier observations had been ignored for decades, and it was only in the 1970's was it shown in a series of studies that inoculation of surgically-removed human cancer tissues into immunodeficient mice, rats or hamsters, followed by poly-passages of the transplanted tumor tissues from one animal to another, can cause sarcomatous transformation of the rodents' stromal cells within the grafted human tumor tissues [205,206,[208][209][210][211][212][213]. The detailed mechanisms underlying this horizontal transformation of malignancy remain nebulous even now.…”
Section: Dissenting Evidence 2: Altered Extracellular Milieu May Init...mentioning
confidence: 99%